DETECTING CHANGES IN COMFORT, PAIN, AND MOBILITY OVER CLINICAL MILESTONES FOR INDIVIDUALS WITH LOWER LIMB LOSS - Brittany Pousett; Charlene C Harasym; Malena Sofia Rapaport; Tessa Richardson; Jesse Spellen; David W Moe; William C Miller (Canadian Prosthetics & Orthotics Journal, 2024)
BACKGROUND: Functional mobility, comfort and the absence of pain are key goals of prosthetic treatment. Outcome measures (OMs) evaluate the impact of treatment and normative and minimal detectable change (MDC) values are key to interpreting these scores and measuring treatment outcomes.